Solar Panel Education as a Renewable Energy System for Students of SMAN 20 Surabaya - Widagdo, Reza Sarwo; Slamet, Puji; Hariadi, Balok; Hartayu, Ratna; Wardah, Izzah Aula (Pelita: Jurnal Pengabdian kepada Masyarakat, 2024)
Introduction of Solar Panels as a Renewable Energy System for high school students in Surabaya City. In particular, the city of Surabaya can be an effort to support the realization of the Sustainable Development Goals (SDGs) program. The team has held online discussions with partners, namely SMAN 20 Surabaya to carry out the introduction of solar panels as a renewable energy system to students at SMAN 20 Surabaya. The purpose of community service is to socialize the use of solar power plants through learning activities (education) and solar power plants training for school students and teachers. The method used in this activity is divided into three stages. In the first stage, field observations were carried out to find problems related to the availability of electrical energy in schools. In the second stage, the implementation of community service includes the delivery of solar panel material with lectures, demonstrations, and the design of solar power plants systems at schools. In the third stage, it is an evaluation or feedback stage by giving questionnaires to participants. The results of this community service activity provide information on understanding solar panels and batteries in the good category. Practical activities need to be taught to student, so solar power plants teaching aids are needed at the school. The team made an educational activity for students, namely a demo of converting solar energy into electrical energy. The implementation of this community service has been carried out well.